Observing Finance as a Network of Observations. Comment on Esposito - Stark, David (Journal of Economic Sociology, 2013)
This essay contributes to observation theory by commenting on Esposito’s paper, «Economic circularities and second-order observation: the reality of ratings». The key question of that paper is summarized as: How does one calculate in the Keynesian third degree (attempting to ascertain what average opinion considers «average opinion» to be) under conditions of diabolical circularity (when uncertainty about the future is generated by attempts to predict it)? Esposito answers that ratings provide a fixed point of reference not because they are accurate but because they are highly visible. The second half of the paper is itself a second-order observation. It uses another viewpoint (that of observation theory) to reinterpret my earlier ethnographic and network analytic research on finance.